Evaluation of Chemical and Physico-Chemical Indicators of Water in the Lakes of Barlinek-Gorzów Landscape Park (North-West Poland) - Daniszewski, Piotr (Asian Journal of Chemistry, 2014)
This paper presents the evaluation of physico-chemical parameters of lake water in the Barlinek-Gorzów Landscape Park based on the European Union Water Framework Directive.The research was carried out in the years 2008-2012, between April and October. From each of the three measuring stations located in the lakes included the study, two separate water samples were taken for chemical analysis. Upon sampling, the water pH was measured. Water was tested in compliance with the Polish Standards. Collected water samples were stabilized pursuant to the guidelines of the Polish Standards. Other indicators of water quality were marked within 24 h of sampling. The oxidation of dissolved organic matter was measured with the COD-Mn method, in accordance with Polish Standards. The pH values in the neutral range-7.48 to 7.85 in all lakes water. According to the classification of the European Union Water Framework Directive, all lakes were classified as first class. The tests have demonstrated that water quality in the lakes with regard to the tested indicators varied. By analyzing the average annual values, one can note that the pH, O2diss. and NO3– concentration showed a relatively small variation in all the investigated lakes. The total suspended solids (TSS) in the lakes Barlineckie, Glebokie, Suche, Lubiszewko, Przyleg and Chlop, fell into the II class, while the lakes Lubie and Wielgie met the criteria of the III class. The Ptotal concentrations in the surface layer of the lakes was little differentiated, reaching the levels appropriate for the II and III quality class according to the classification of the European Union Water Framework Directive. The total phosphorus concentration was 0.21-0.67 mg dm-3. The highest concentration of total phosphorus was recorded in Lakes Przyleg and Wielgie. The total suspended solids in the lakes Barlineckie, Glebokie, Suche, Lubiszewko, Przyleg and Chlop, fell into the II class, while the lakes Lubie and Wielgie met the criteria of the III class. The Ptotal concentrations in the surface layer of the lakes was little differentiated, reaching the levels appropriate for the II and III quality class according to the classification of the European Union Water Framework Directive.